2018
DOI: 10.1007/s12032-018-1173-9
|View full text |Cite
|
Sign up to set email alerts
|

A population-based analysis of urban–rural disparities in advanced pancreatic cancer management and outcomes

Abstract: Given the significant morbidity burden associated with advanced pancreatic cancer (APC), its management is complex and frequently requires multidisciplinary care. Because of potential geographical barriers to healthcare access, we aimed to determine the effect of rurality on management and outcomes of APC patients. Patients diagnosed with APC from 2008 to 2015 and received Gemcitabine (Gem), Gemcitabine plus nab-Paclitaxel (Gem/Nab), or FOLFIRINOX at any 1 of 6 British Columbia cancer centers across the provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…A geographic analysis of advanced pancreatic cancer found no difference in survival between rural and urban residence, albeit within a sample of patients who had already received chemotherapy, with some having undergone curative-intent resection. 53 A different study of unresected pancreatic cancer indicated that rural living negatively impacted oncology consultation but not receipt of chemotherapy. 54 A similar pattern was also observed for radiation therapy delivery, whereby greater distance was inversely associated with radiation oncology consultation but not with receipt of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A geographic analysis of advanced pancreatic cancer found no difference in survival between rural and urban residence, albeit within a sample of patients who had already received chemotherapy, with some having undergone curative-intent resection. 53 A different study of unresected pancreatic cancer indicated that rural living negatively impacted oncology consultation but not receipt of chemotherapy. 54 A similar pattern was also observed for radiation therapy delivery, whereby greater distance was inversely associated with radiation oncology consultation but not with receipt of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have most commonly addressed acceptability of therapy by focusing on patients receiving chemotherapy and describing the use of different regi mens. 14,[30][31][32] Some small studies that examined referral patterns were limited by smaller sample sizes or also encompassed cura tive management, which confused the results. 11,12 Rates of medi cal oncology consultations for noncurative pancreatic adenocar cinoma have been reported at 31% in Nova Scotia and 54% in Alberta, with older age and higher comorbidity burden associ ated with no consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted that rural pancreatic cancer patients tend to experience worse survival rates even after controlling for a number of patient factors 7,12‐15 . The 2 exceptions that show limited differences in survival by rurality are based outside of the United States, 16,17 where the different health care systems may explain the lack of disparities. One potential factor that could be contributing to worse survival outcomes in rural patients is later stage of diagnosis, the focus of the current study.…”
mentioning
confidence: 99%